KINERJA APARATUR DALAM PELAYANAN DI KANTOR BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN KUTAI BARAT - Regina Deasy Marlina (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
The purpose of this study is to describe and analyze the performance of personnel in the public service in the Office of Financial Management and Asset Kutai Barat. The analysis used in this research is the data analysis interactive model by three (3) lines of activities occurring simultaneously, namely condensation, data presentation and conclusion/verification. The study concluded that the performance of the apparatus in an effort to improve the service has been good, although not optimal, however the services provided have shown progress, this is due to several things: the ability to use working hours in efektf, the quality of the work produced then the responsiveness of employees is good enough.Keyword: apparatur performance, service, management